Review of Histopathological Diagnoses of One Year Appendectomy Specimens in Sulaimani City - yaseen, Hadeel; khudaier, Hassanain; Ibrahim, ali (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To review and see the pattern of histopathological diagnoses of one year appendectomy specimens. Methodology: This retrospective study was carried in Sulaimani Teaching Hospital over the period of one year (from 1st of January to 31st of December 2009). All pathological reports were reviewed retrospectively for patient’s age, sex, histopathological diagnosis and operative findings (if present). Histopathological diagnoses then were classified into either positive or negative for acute inflammation. Any associated findings or any surgical specimen removed with the appendix was recorded. The obtained data were analyzed by using the statistical package social sciences (SPSS) version 19; with Chi square to test for significance between data. Results: Hospital pathological reports of 2052 appendectomy cases were reviewed, (47.12%) were males and (52.88%) were females. 61.9% of all appendectomy cases were positive for acute inflammation (32.9% had acute appendicitis; 26.1 % had acute suppurative appendicitis , and 4.5% had gangrenous appendicitis), while 38.1% were negative (28.5 % had reactive follicular hyperplasia, 6.2% were normal, and 0.2% had carcinoid tumors). Negative for acute inflammation cases were generally significantly more common in females e.g. periappendicitis, Reactive Follicular Hyperplesia and carcinoid tumor but eosinophilic appendicitis cases like acute appendicitis were more common in males. Normal appendixes versus Reactive Follicular Hyperplesia (without associated appendicitis) are two entities that intermingle. Chronic appendicitis is controversial entity. Out of 20 cases with Entrobius vermicularis (95%) cases were associated with reactive follicular hyperplasia and it shows non significant association with acute appendicitis. Recommendation: We recommend that the pathologists must be strict to histological criteria for each pathological entity before the diagnosis.